Duck & company - Caple, Kathy (New York : Holiday House, 2007)
Rat and Duck run a bookshop and work to find the right book for each of their customers.
Accelerated Reader AR
Keywords: Bookstores -- Juvenile fiction; Rats -- Juvenile fiction; Ducks -- Juvenile fiction